Metal catalyst for acceptor-free alcohol dehydrogenation reaction and preparation method thereof

By adopting the Ni-Cu bimetallic catalyst system in the dehydrogenation reaction of acceptor-free alcohol, the problem of difficult separation and recovery of homogeneous catalysts is solved, and the catalytic effect with high selectivity and stability is achieved, and the catalyst preparation process is simplified. Improves activity and recyclability.

CN119259053APending Publication Date: 2025-01-07TAN KAH KEE INNOVATION LAB +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411371867.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing homogeneous metal catalysts have difficulties in separation and recycling in the dehydrogenation reaction of acceptor-free alcohols, which limits the sustainable and large-scale application of the catalyst.

Method used

Using the bimetallic catalyst systems Ni and Cu, the nickel and copper precursors and silicon precursors are synthesized under oil bath conditions by preparation method to form a Ni-Cu alloy and encapsulate it in SiO2 to improve the selectivity and stability of the catalyst.

Benefits of technology

The high selectivity and stability of the catalyst in the dehydrogenation reaction of acceptor-free alcohol is achieved, the catalyst preparation process is simplified, and the activity and recyclability of the catalyst are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259053A_ABST
    Figure CN119259053A_ABST
Patent Text Reader

Abstract

The invention provides a metal catalyst for an acceptor-free alcohol dehydrogenation reaction and a preparation method of the metal catalyst, and relates to the technical field of metal catalysts. The metal catalyst for the acceptor-free alcohol dehydrogenation reaction is a double-metal system, and double metals comprise Ni and Cu. The bimetallic catalyst provided by the invention has excellent catalytic activity and selectivity in an acceptor-free alcohol dehydrogenation reaction, and compared with an existing nickel metal catalytic system, the bimetallic catalyst has the technical advantages of being good in selectivity and stable in catalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal catalysts, in particular to a metal catalyst for receptor-free alcohol dehydrogenation reaction and a preparation method thereof. Background Art

[0002] The acceptor-free dehydrogenation (AD) reaction of organic compounds has attracted wide attention because it is both "green" and "sustainable". Compared with the traditional dehydrogenation reaction of organic compounds, the AD reaction does not require the use of conventional oxidants or acceptors (such as metal oxygen reagents, peroxides, perchlorates, hypervalent iodine and molecular oxygen, etc.), so it can greatly reduce the generation of waste and improve the atomic economy of the reaction.

[0003] In addition, this reaction is also highly relevant to the field of organic hydrogen storage materials, and can directly use biomass or its fermentation products to produce hydrogen, which is crucial to the development of the hydrogen industry. Currently, among various types of AD reactions, the acceptor-free alcohol dehydrogenation (AAD) reaction has received more extensive attention due to the availability and low cost of alcohols. Through the AAD reaction, not only hydrogen can be produced, but also aldehydes with high added value can be produced.

[0004] Although a large number of homogeneous metal catalysts have been developed to catalyze the AAD reaction and show excellent catalytic activity and selectivity, homogeneous catalysts usually face the problems of difficult separation and recovery, which greatly limits the sustainable and large-scale application of catalysts.

[0005] Therefore, it is crucial to design and develop heterogeneous catalysts with high activity, high selectivity, high stability and recyclability.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The first object of the present invention is to provide a metal catalyst for acceptor-free alcohol dehydrogenation reaction, which has excellent catalytic selectivity in the acceptor-free alcohol dehydrogenation reaction and has the technical advantages of good selectivity and catalytic stability compared with the existing nickel metal catalytic system.

[0008] The second object of the present invention is to provide a method for preparing a metal catalyst for acceptor-free alcohol dehydrogenation reaction.

[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0010] The present invention provides a metal catalyst for receptor-free alcohol dehydrogenation reaction, wherein the metal catalyst is a bimetallic system, wherein:

[0011] The bimetal includes Ni and Cu.

[0012] Furthermore, the structural formula of the metal catalyst is Ni x Cu y @SiO2, where 1≤x≤6, 0<y≤5.

[0013] Furthermore, the structural formula of the metal catalyst is Ni3Cu3@SiO2.

[0014] The present invention provides a method for preparing the above-mentioned metal catalyst for receptor-free alcohol dehydrogenation reaction, the preparation method comprising:

[0015] (A) providing a solution A obtained by mixing CA-630 and cyclohexane, and then sequentially adding a mixed aqueous solution containing a nickel precursor and a copper precursor, concentrated ammonia water, and a silicon precursor dropwise into the solution A to obtain a solution B;

[0016] (B) placing the solution B obtained in step (A) in an oil bath at 30-100° C. for 5-20 hours, then dispersing it in an ethanol solution, and sequentially washing, centrifuging, and drying to obtain a catalyst precursor;

[0017] (C) reducing the catalyst precursor obtained in step (B) under a hydrogen atmosphere to obtain a metal catalyst.

[0018] Further, the nickel precursor is at least one of nickel chloride hexahydrate, nickel nitrate hexahydrate or nickel sulfate hexahydrate;

[0019] The copper precursor is at least one of copper chloride hexahydrate, copper nitrate hexahydrate or copper sulfate hexahydrate.

[0020] Furthermore, the concentrated ammonia water is a 25% to 28% ammonia water solution.

[0021] Furthermore, the silicon precursor is any one of tetraethyl orthosilicate or silica sol.

[0022] Furthermore, in the step (A), the volume ratio of the mixed aqueous solution containing the nickel precursor and the copper precursor, the concentrated ammonia water, and the silicon precursor is (1-5):(2-9):(2-9).

[0023] Furthermore, the hydrogen atmosphere is a mixed gas containing 5% to 40% hydrogen, and the mixed gas consists of hydrogen, argon and nitrogen;

[0024] The reduction is carried out in the hydrogen atmosphere at a temperature of 300 to 700° C. and for a time of 1 to 4 hours.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention provides a metal catalyst for a receptor-free alcohol dehydrogenation reaction, wherein the metal catalyst is a bimetallic system. The bimetallic includes Ni and Cu. The bimetallic catalyst provided by the present application has excellent catalytic selectivity in the receptor-free alcohol dehydrogenation reaction, and has the technical advantages of good selectivity and stable catalysis compared to the existing nickel metal catalytic system.

[0027] The invention provides a method for preparing a metal catalyst for a receptor-free alcohol dehydrogenation reaction. The method comprises the following steps: firstly, a mixed aqueous solution containing a nickel precursor and a copper precursor, concentrated ammonia water, and a silicon precursor are sequentially added dropwise to a mixed solution consisting of CA-630 and cyclohexane; and then the mixture is prepared by an oil bath. The method has the technical advantages of a mild preparation process and a high catalyst yield, and is convenient for realizing the large-scale production of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 This is the X-ray diffraction pattern of the bimetallic catalyst Ni3Cu3@SiO2(H500) prepared in Example 1 of the present invention;

[0030] Figure 2 This is an in-situ infrared image of CO adsorption of the bimetallic catalyst Ni3Cu3@SiO2(H500) prepared in Example 1 of the present invention;

[0031] Figure 3 TEM electron microscope image and particle size statistical histogram of the bimetallic catalyst Ni3Cu3@SiO2(H500) prepared in Example 1 of the present invention;

[0032] Figure 4 This is a performance test diagram of the benzyl alcohol dehydrogenation reaction of the catalysts prepared in Examples 1 to 5 of the present invention and Comparative Examples 1 and 2;

[0033] Figure 5 This is a diagram for evaluating the recyclability of benzyl alcohol dehydrogenation using the catalyst Ni3Cu3@SiO2 (H500) prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0034] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] According to one aspect of the present invention, a metal catalyst for acceptor-free alcohol dehydrogenation reaction, the metal catalyst is a bimetallic system, wherein:

[0036] The bimetal includes Ni and Cu.

[0037] The present invention provides a metal catalyst for a receptor-free alcohol dehydrogenation reaction, wherein the metal catalyst is a bimetallic system. The bimetallic includes Ni and Cu. The bimetallic catalyst provided by the present application has excellent catalytic selectivity in the receptor-free alcohol dehydrogenation reaction, and can realize the high-selectivity production of the corresponding aldehyde using alcohol, and can directly prepare gaseous hydrogen; compared with the existing nickel metal catalytic system, it has the technical advantages of good selectivity and stable catalysis.

[0038] It should be noted that nickel-based catalysts have been used in a variety of catalytic reactions including water gas change reaction, ammonia decomposition reaction, methane dry reforming reaction, aldehyde\ketone reduction amination reaction, and have shown excellent catalytic activity. However, nickel-based catalysts also have some common shortcomings, such as easy sintering, poor selectivity, easy to produce carbon deposits and easy oxidation. This has driven a large number of researchers to explore new methods to solve these problems in nickel-based catalysts. The present application introduces a modification strategy of a bimetallic catalyst system into a Ni-based catalytic system, which has been verified to not only improve the catalytic selectivity of the receptor-free alcohol dehydrogenation reaction, but also improve the activity and stability of the catalyst.

[0039] It should be noted that the advantages of the catalyst of the present application being high in activity and strong in stability are that Ni and Cu in the bimetallic catalyst of the present application can form an alloy and be wrapped by SiO2, because Ni and Cu can simultaneously form layered silicates under the catalyst preparation conditions, which makes it easier for Ni and Cu to form an alloy structure during the reduction process and be wrapped in SiO2. On the other hand, Fe and Co are difficult to form corresponding layered silicates under the catalyst preparation conditions, and thus are difficult to form an alloy with Ni that is similar to the effect of Cu and is wrapped in SiO2.

[0040] In a preferred embodiment of the present invention, the structural formula of the metal catalyst is Ni x Cu y @SiO2, where 1≤x≤6, 0<y≤5.

[0041] Furthermore, the structural formula of the metal catalyst is Ni3Cu3@SiO2.

[0042] As a preferred embodiment, the molar ratio of Ni to Cu in the metal catalyst is (1-6):(0-5), preferably 3:3.

[0043] According to one aspect of the present invention, a method for preparing the above-mentioned metal catalyst for acceptor-free alcohol dehydrogenation reaction comprises:

[0044] (A) providing a solution A obtained by mixing CA-630 and cyclohexane, and then sequentially adding a mixed aqueous solution containing a nickel precursor and a copper precursor, concentrated ammonia water, and a silicon precursor dropwise into the solution A to obtain a solution B;

[0045] (B) placing the solution B obtained in step (A) in an oil bath at 30-100° C. for 5-20 hours, then dispersing it in an ethanol solution, and sequentially washing, centrifuging, and drying to obtain a catalyst precursor;

[0046] (C) reducing the catalyst precursor obtained in step (B) under a hydrogen atmosphere to obtain a metal catalyst.

[0047] The invention provides a method for preparing a metal catalyst for a receptor-free alcohol dehydrogenation reaction. The method comprises the following steps: firstly, a mixed aqueous solution containing a nickel precursor and a copper precursor, concentrated ammonia water, and a silicon precursor are sequentially added dropwise to a mixed solution consisting of CA-630 and cyclohexane; and then the mixture is prepared by an oil bath. The method has the technical advantages of a mild preparation process and a high catalyst yield, and is convenient for realizing the large-scale production of the catalyst.

[0048] In a preferred embodiment of the present invention, the nickel precursor is at least one of nickel chloride hexahydrate, nickel nitrate hexahydrate or nickel sulfate hexahydrate;

[0049] The copper precursor is at least one of copper chloride hexahydrate, copper nitrate hexahydrate or copper sulfate hexahydrate.

[0050] In a preferred embodiment of the present invention, the concentrated ammonia water is a 25% to 28% ammonia water solution.

[0051] In a preferred embodiment of the present invention, the silicon precursor is any one of tetraethyl orthosilicate or silica sol.

[0052] In a preferred embodiment of the present invention, the volume ratio of the mixed aqueous solution containing the nickel precursor and the copper precursor, the concentrated ammonia water, and the silicon precursor in step (A) is (1-5):(2-9):(2-9).

[0053] In the above preferred embodiment, the hydrogen atmosphere is a mixed gas containing 5% to 40% hydrogen, and the mixed gas consists of hydrogen, argon and nitrogen;

[0054] The reduction is carried out in the hydrogen atmosphere at a temperature of 300 to 700° C. and for a time of 1 to 4 hours.

[0055] The technical solution of the present invention will be further described below in conjunction with embodiments.

[0056] Example 1

[0057] Preparation of bimetallic catalyst system Ni3Cu3@SiO2(H500):

[0058] (1) Mix 25 mL of CA-630 and 25 mL of cyclohexane in a round-bottom flask and stir thoroughly;

[0059] (2) 2.0 mL Ni(NO3)2·6H2O and Cu(NO3) 2· 6H2O (Ni:Cu molar ratio is 3:3) mixed aqueous solution (70wt%) was slowly added dropwise to the above solution and stirred until the solution became transparent;

[0060] (3) Slowly add 5.0 mL of concentrated aqueous ammonia (25-28 wt%) and stir for about 5 min;

[0061] (4) Slowly add 5.0 mL of tetraethyl orthosilicate, place the round-bottom flask in a 60°C water bath, and stir for 12 h until the solution becomes viscous;

[0062] (5) dispersing it in an ethanol solution, washing it, centrifuging it 5 times, and then placing it in a drying oven to dry for about 12 hours, taking it out, and grinding it to obtain the precursor of the target catalyst;

[0063] (6) The catalyst precursor was placed in a H2 / Ar (v / v = 1 / 3) atmosphere for reduction (reduction conditions: 10 °C min -1 , 500℃, 2h), and the target catalyst Ni3Cu3@SiO2(H500) was obtained.

[0064] Example 2

[0065] Preparation of bimetallic catalyst system Ni5Cu1@SiO2(H500):

[0066] (1) Same as Example 1;

[0067] (2) 2.0 mL Ni(NO3)2·6H2O and Cu(NO3) 2·6H2O (Ni:Cu molar ratio is 5:1) mixed aqueous solution (70wt%) was slowly added dropwise to the above solution and stirred until the solution became transparent;

[0068] (3) Same as Example 1;

[0069] (4) Same as Example 1;

[0070] (5) Same as Example 1;

[0071] (6) The catalyst precursor was placed in a H2 / Ar (v / v = 1 / 3) atmosphere for reduction (reduction conditions: 10 °C min -1 , 500℃, 2h), and the target catalyst Ni5Cu1@SiO2(H500) was obtained.

[0072] Example 3

[0073] Preparation of bimetallic catalyst system Ni4Cu2@SiO2(H500):

[0074] (1) Same as Example 1;

[0075] (2) 2.0 mL Ni(NO3)2·6H2O and Cu(NO3) 2· 6H2O (Ni:Cu molar ratio is 4:2) mixed aqueous solution (70wt%) was slowly added dropwise to the above solution and stirred until the solution became transparent;

[0076] (3) Same as Example 1;

[0077] (4) Same as Example 1;

[0078] (5) Same as Example 1;

[0079] (6) The catalyst precursor was placed in a H2 / Ar (v / v = 1 / 3) atmosphere for reduction (reduction conditions: 10 °C min -1 , 500℃, 2h), and the target catalyst Ni4Cu2@SiO2(H500) was obtained.

[0080] Example 4

[0081] Preparation of Bimetallic Catalytic System Ni2Cu4@SiO2(H500)

[0082] (1) Same as Example 1;

[0083] (2) 2.0 mL Ni(NO3)2·6H2O and Cu(NO3) 2· 6H2O (Ni:Cu molar ratio is 2:4) mixed aqueous solution (70wt%) was slowly added dropwise to the above solution and stirred until the solution became transparent;

[0084] (3) Same as Example 1;

[0085] (4) Same as Example 1;

[0086] (5) Same as Example 1;

[0087] (6) The catalyst precursor was placed in a H2 / Ar (v / v = 1 / 3) atmosphere for reduction (reduction conditions: 10 °C min -1 , 500℃, 2h), and the target catalyst Ni2Cu4@SiO2(H500) was obtained.

[0088] Example 5

[0089] Preparation of Bimetallic Catalytic System Ni1Cu5@SiO2(H500)

[0090] (1) Same as Example 1;

[0091] (2) 2.0 mL Ni(NO3)2·6H2O and Cu(NO3) 2· 6H2O (Ni:Cu molar ratio is 1:5) mixed aqueous solution (70wt%) was slowly added dropwise to the above solution and stirred until the solution became transparent;

[0092] (3) Same as Example 1;

[0093] (4) Same as Example 1;

[0094] (5) Same as Example 1;

[0095] (6) The catalyst precursor was placed in a H2 / Ar (v / v = 1 / 3) atmosphere for reduction (reduction conditions: 10 °C min -1 , 500℃, 2h), and the target catalyst Ni1Cu5@SiO2(H500) was obtained.

[0096] Comparative Example 1

[0097] Preparation of metal catalyst Ni@SiO2(H500):

[0098] (1) Same as Example 1;

[0099] (2) 2.0 mL of Ni(NO3)2·6H2O aqueous solution (70 wt%) was slowly added dropwise to the above solution and stirred until the solution became transparent;

[0100] (3) Same as Example 1;

[0101] (4) Same as Example 1;

[0102] (5) Same as Example 1;

[0103] (6) The catalyst precursor was placed in a H2 / Ar (v / v = 1 / 3) atmosphere for reduction (reduction conditions: 10 °C min -1 , 500℃, 2h), and the target catalyst Ni@SiO2(H500) was obtained.

[0104] Comparative Example 2

[0105] Preparation of metal catalyst Cu@SiO2(H500):

[0106] (1) Same as Example 1;

[0107] (2) 2.0 mL of Cu(NO3)2·6H2O aqueous solution (70 wt%) was slowly added dropwise to the above solution and stirred until the solution became transparent;

[0108] (3) Same as Example 1;

[0109] (4) Same as Example 1;

[0110] (5) Same as Example 1;

[0111] (6) The catalyst precursor was placed in a H2 / Ar (v / v = 1 / 3) atmosphere for reduction (reduction conditions: 10 °C min -1 , 500℃, 2h), and the target catalyst Cu@SiO2(H500) was obtained.

[0112] Comparative Example 3

[0113] In this comparative example, step (2) is changed to:

[0114] (2) Mix 2.0 mL Ni(NO3)2·6H2O and Fe(NO3) 3· 9H2O (Ni:Fe molar ratio is 3:3) mixed aqueous solution (70wt%) was slowly added dropwise to the above solution and stirred until the solution became transparent;

[0115] The rest is the same as in Example 1.

[0116] Comparative Example 4

[0117] In this comparative example, step (2) is changed to:

[0118] (2) 2.0 mL Ni(NO3)2·6H2O and Co(NO3) 2· 6H2O (Ni:Co molar ratio is 3:3) mixed aqueous solution (70wt%) was slowly added dropwise to the above solution and stirred until the solution became transparent;

[0119] The rest is the same as in Example 1.

[0120] Test Example 1

[0121] In order to characterize the structure of the bimetallic catalytic system of the catalyst of the present application, the bimetallic catalyst Ni3Cu3@SiO2(H500) prepared in Example 1 of the present application is structurally characterized as follows:

[0122] (1) Take about 50 mg of Ni3Cu3@SiO2 (H500) catalyst and perform X-ray diffraction (XRD) experiment.

[0123] Figure 1 This is the X-ray diffraction pattern of the bimetallic catalyst Ni3Cu3@SiO2(H500) prepared in Example 1.

[0124] Depend on Figure 1 It can be seen that the metal nanoparticles in Ni3Cu3@SiO2(H500) are a Ni-Cu alloy structure. From the X-ray diffraction pattern, it can be seen that the crystal plane diffraction peak of the sample appears between the standard peaks of Ni and Cu, proving the formation of Ni-Cu alloy.

[0125] (2) Take about 50 mg of Ni3Cu3@SiO2(H500) catalyst and conduct in situ infrared experiment of CO adsorption.

[0126] Figure 2 This is the in-situ infrared image of CO adsorption of the bimetallic catalyst Ni3Cu3@SiO2(H500) prepared in Example 1.

[0127] from Figure 2 It can be seen that there is only a linear adsorption peak of CO on the catalyst surface, indicating that the Ni metal sites in the catalyst forming the Ni-Cu alloy are dispersed, which also confirms the formation of the Ni-Cu alloy structure from the side.

[0128] (3) About 1 mg of Ni3Cu3@SiO2 (H500) catalyst was dispersed in an ethanol solution and subjected to ultrasonic dispersion for about 30 min. Finally, a small amount of the sample ethanol solution was taken out and dropped onto the surface of the ultra-thin carbon film for transmission electron microscopy (TEM) experiments and particle size statistics.

[0129] Figure 3 The TEM image and particle size statistical histogram of the bimetallic catalyst Ni3Cu3@SiO2 (H500) prepared in Example 1. Figure 3 Figure a is the TEM image of the bimetallic catalyst Ni3Cu3@SiO2(H500); Figure 3 (b) is the particle size statistical histogram of the bimetallic catalyst Ni3Cu3@SiO2(H500).

[0130] Depend on Figure 3 It can be seen from the transmission electron microscope image that the metal nanoparticles of the sample are relatively uniform, and the average particle size of 200 particles is about 4.27nm.

[0131] Test Example 2

[0132] (1) The activity and selectivity of the benzyl alcohol dehydrogenation reaction were tested using the catalysts prepared in Examples 1 to 5 and Comparative Examples 1 to 4 of the present application. The specific method is as follows:

[0133] First, the substrate (benzyl alcohol) and the solvent (mesitylene) were mixed in a 50 mL two-necked round-bottom flask (4 mmol benzyl alcohol + 10 mL mesitylene); second, the air in the round-bottom flask was continuously purged with argon while stirring, and the mixture was heated to 130°C; then, 50 mg of the previously reduced catalyst was quickly transferred to the round-bottom flask (try to avoid contact with air during the transfer process); argon was used to purge the mixture during the entire reaction and condensed using a condenser. The sample was collected by syringe extraction and then detected by gas chromatography (GC9790, Fuli, FID detector, KB-INNO WAX column).

[0134] See Table 1 for specific results.

[0135] Table 1: Comparison of the activity and selectivity test results of the catalysts prepared in Examples 1 to 5 and Comparative Examples 1 to 4 for the dehydrogenation of benzyl alcohol

[0136] Group 600min conversion rate (%) 600min selectivity (%) Example 1 99.2 98.3 Example 2 99.1 49.8 Example 3 99.2 67.8 Example 4 73.9 98.4 Example 5 14.7 - Comparative Example 1 99.2 46.9 Comparative Example 2 <10.0 - Comparative Example 3 89.6 50.8 Comparative Example 4 88.1 52.3

[0137] Figure 4 This is a performance test diagram of the catalysts prepared in Examples 1 to 5 and Comparative Examples 1 and 2 for the dehydrogenation reaction of benzyl alcohol. Figure 4 Figure a is a performance test diagram of the catalyst Ni@SiO2 (H500) of Comparative Example 1; Figure 4 b is a performance test diagram of the catalyst Ni5Cu1@SiO2 (H500) of Example 2;

[0138] Figure 4 Figure c is a performance test diagram of the catalyst Ni4Cu2@SiO2 (H500) of Example 3; Figure 4 Figure d is a performance test diagram of the catalyst Ni3Cu3@SiO2 (H500) of Example 1; Figure 4 Figure e is a performance test diagram of the catalyst Ni2Cu4@SiO2 (H500) of Example 4; Figure 4 Figure f is a performance test diagram of the catalyst Ni1Cu5@SiO2 (H500) of Example 5.

[0139] from Figure 4 It can be seen that in Nix Cu y In the @SiO2 catalytic system, the selectivity of the catalyst gradually increases with the increase of Cu content. In the Ni3Cu3@SiO2 (H500) catalyst sample, the activity and selectivity of benzyl alcohol dehydrogenation to prepare benzaldehyde simultaneously reach a high level (600min, conversion rate>99%, selectivity>98%).

[0140] (2) Weigh 50 mg of the catalyst Ni3Cu3@SiO2 (H500) prepared in Example 1 and perform a cyclic test on the dehydrogenation reaction of benzyl alcohol.

[0141] Figure 5 This is the evaluation diagram of the recyclability of benzyl alcohol dehydrogenation of the catalyst Ni3Cu3@SiO2 (H500) prepared in Example 1.

[0142] from Figure 5 It can be seen that during the 6 cycles, the conversion rate and selectivity of benzyl alcohol dehydrogenation to prepare benzaldehyde did not show a significant decrease, indicating that the catalytic system has good stability and recyclability during use.

[0143] (3) Weigh 50 mg of the catalyst Ni3Cu3@SiO2 (H500) prepared in Example 1 and test the dehydrogenation activity and selectivity of other alcohols, as shown in Table 2.

[0144] Table 2: Comparison of catalytic performance of Ni3Cu3@SiO2 catalytic samples on other types of alcohols

[0145]

[0146]

[0147] As can be seen from Table 2, the Ni3Cu3@SiO2 catalytic sample exhibits excellent selectivity for many other alcohols, further indicating that this catalytic system is universal for the highly selective dehydrogenation of alcohols to produce aldehydes.

[0148] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A metal catalyst for acceptor-free alcohol dehydrogenation reaction, characterized in that: The metal catalyst is a bimetallic system, wherein: The bimetal includes Ni and Cu.

2. The metal catalyst for acceptor-free alcohol dehydrogenation reaction according to claim 1, characterized in that: The structural formula of the metal catalyst is Ni x Cu y @SiO2, where 1≤x≤6, 0<y≤5.

3. The metal catalyst for acceptor-free alcohol dehydrogenation reaction according to claim 2, characterized in that: The structural formula of the metal catalyst is Ni3Cu3@SiO2.

4. A method for preparing a metal catalyst for acceptor-free alcohol dehydrogenation reaction according to any one of claims 1 to 3, characterized in that: The preparation method comprises: (A) providing a solution A obtained by mixing CA-630 and cyclohexane, and then sequentially adding a mixed aqueous solution containing a nickel precursor and a copper precursor, concentrated ammonia water, and a silicon precursor dropwise into the solution A to obtain a solution B; (B) placing the solution B obtained in step (A) in an oil bath at 30-100° C. for 5-20 hours, then dispersing it in an ethanol solution, and sequentially washing, centrifuging, and drying to obtain a catalyst precursor; (C) reducing the catalyst precursor obtained in step (B) under a hydrogen atmosphere to obtain a metal catalyst.

5. The method for preparing a metal catalyst for acceptor-free alcohol dehydrogenation reaction according to claim 4, characterized in that: The nickel precursor is at least one of nickel chloride hexahydrate, nickel nitrate hexahydrate or nickel sulfate hexahydrate; The copper precursor is at least one of copper chloride hexahydrate, copper nitrate hexahydrate or copper sulfate hexahydrate.

6. The method for preparing a metal catalyst for acceptor-free alcohol dehydrogenation reaction according to claim 4, characterized in that: The concentrated ammonia water is a 25% to 28% ammonia water solution.

7. The method for preparing a metal catalyst for acceptor-free alcohol dehydrogenation reaction according to claim 4, characterized in that: The silicon precursor is at least one of tetraethyl orthosilicate and silica sol.

8. The method for preparing a metal catalyst for acceptor-free alcohol dehydrogenation reaction according to claim 4, characterized in that: The volume ratio of the mixed aqueous solution containing nickel precursor and copper precursor, concentrated ammonia water and silicon precursor in step (A) is (1-5):(2-9):(2-9).

9. The method for preparing a metal catalyst for acceptor-free alcohol dehydrogenation reaction according to claim 4, characterized in that: The hydrogen atmosphere is a mixed gas containing 5% to 40% hydrogen, and the mixed gas is composed of hydrogen, argon and nitrogen; The temperature for reduction in the hydrogen atmosphere is 300-700° C. and the time is 1-4 hours.